2006
DOI: 10.1093/jxb/erj085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of defoliation intensity and frequency on N uptake and mobilization in Lolium perenne

Abstract: The aim of the study was to evaluate the impact of defoliation intensity, defoliation frequency, and interactions with N supply on N uptake, N mobilization from and N allocation to roots, adult leaves, and growing leaves. Plants of Lolium perenne were grown under two contrasted N regimes. Defoliation intensity treatments consisted of a range of percentage leaf area removal (0, 25, 50, 75, or 100%). These treatments were applied in parallel to a set of plants previously undefoliated, and to a second set of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 29 publications
2
51
1
3
Order By: Relevance
“…Lestienne et al (2006) observed no effect of final defoliation intensity on labelled N allocated to growing leaves of Lolium perenne, but also found a decrease in labelled N allocated to roots when 100 % leaf area was removed.…”
Section: Nitrogen Allocationmentioning
confidence: 71%
See 4 more Smart Citations
“…Lestienne et al (2006) observed no effect of final defoliation intensity on labelled N allocated to growing leaves of Lolium perenne, but also found a decrease in labelled N allocated to roots when 100 % leaf area was removed.…”
Section: Nitrogen Allocationmentioning
confidence: 71%
“…In the present experiment, roots were source of N for mobilisation just when plants were defoliated on day 0 and became a sink for mobilized N when plants initially cut to a 0.30 m height were not subjected to a final defoliation (0 % leaf area removal on day 0). Lestienne et al (2006) observed that roots were a net source of N and that increasing defoliation severity of L. perenne did not change the amount of N mobilised to young leaves, reliant on an increase in the contribution of roots supplying mobilised N to growing leaves. Taken together results of Lestienne et al (2006) and the current study suggest a different effect of defoliation on source/sink relations of P. maximum and L. perenne.…”
Section: Nitrogen Allocationmentioning
confidence: 90%
See 3 more Smart Citations